Senescence-Associated Secretory Phenotype as a Hinge Between Cardiovascular Diseases and Cancer - Banerjee, Priyanka; Kotla, Sivareddy; Reddy Velatooru, Loka; Abe, Rei J.; Davis, Elizabeth A.; Cooke, John P.; Schadler, Keri; Deswal, Anita; Herrmann, Joerg; Lin, Steven H.; Abe, Jun-ichi; Le, Nhat-Tu (Frontiers in Cardiovascular Medicine, 2021)
The role of senescence in the development of cancer and cardiovascular diseases (CVDs) has been established, but its role as the point of interconnection between these diseases remains unclear. Senescence was originally characterized by an irreversible cell cycle arrest after a high number of divisions, namely replicative senescence (RS). However, it is becoming clear that senescence can also be instigated by stresses, so-called stress-induced premature senescence (SIPS). Telomere shortening is a hallmark of RS. The contribution of telomere DNA damage and subsequent DNA damage response/repair to SIPS has also been suggested. Although cellular senescence can mediate cell cycle arrest, senescent cells can also remain metabolically active and secrete cytokines, chemokines, growth factors, and reactive oxygen species (ROS), so-called senescence-associated secretory phenotype (SASP). The involvement of SASP in both cancer and CVDs has been established. In patients with cancer or CVDs, SASP is induced by various stressors including cancer treatments, pro-inflammatory cytokines, and ROS. Therefore, SASP can be the point of interconnection between cancer and CVDs. Importantly, the conventional concept of senescence as the mediator of cell cycle arrest has been challenged, as it was recently reported that chemotherapy-induced senescence can reprogram senescent cancer cells to acquire “stemness” (SAS: senescence-associated stemness). SAS allows senescent cancer cells to escape cell cycle arrest with strongly enhanced clonogenic growth capacity. SAS supports senescent cells to promote both cancer and CVDs, particularly in highly stressful conditions such as cancer treatments, myocardial infarction, and heart failure. Therefore, it is critical to study the mechanisms by which these senescence pathways (SAS/SASP) are induced and regulated in both cancer and CVDs.